Clinical-epidemiological profile and metabolic syndrome in adult patients treated in a Peruvian jungle area - Ramirez-Retis, Ingrid Yasminda (2023)
Objective. To identify the clinical-epidemiological profle of the metabolic syndrome in adult patients treated in a Peruvian jungle area. Methods. Thestudy was observational, retrospective, cross-sectional, qualitative approach, descriptive level and design. The sample consisted of 300 adult patients; the type of sampling was non-probabilistic by convenience. The technique used was the documentation of clinical histories. Six experts were used to validate the instrument. Finally, the principles of beneficence and confdentiality were considered. Results. It was also evident that 55.7 % of the adult patients attended had the presence of metabolic syndrome based on the clinical profle, expressed by means of the chi-square test (x2 =13.653; P = <0.05), which was statistically signifcant. Conclusions. Metabolic syndrome exists on the basis of the clinicalepidemiological profle in adult patients seen at the medical post.